(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Crohn’s disease is an incurable progressive disease of the gastrointestinal tract, in which up to 90% of patients undergo one or more operations during their life. Despite the active development and introduction of new surgical techniques for the treatment of patients with Crohn’s disease, there is still a high incidence of postoperative complications - up to 25-30%. The problems of influence of various factors on the results of surgical interventions in children with Crohn’s disease are still very controversial.